Successful Brincidofovir Treatment of Metagenomics-detected Adenovirus Infection in a Severely Ill Signal Transducer and Activator of Transcription-1-deficient Patient. Issue 3 (March 2019) - Averbuch, Diana; Safadi, Rifaat; Dar, Daniel; Wolf, Dana; Cherniak, Meir; Sorek, Rotem; Amit, Sharon
Abstract : A signal transducer and activator of transcription-1-deficient patient presented with prolonged fever, cachexia, anemia, hypoalbuminemia and finally relapsing debilitating mycobacterial osteomyelitis while receiving a previously effective antimycobacterial treatment. Progression despite rigorous workup and multiple antibiotics prompted shotgun metagenomics revealing adenovirus in liver samples. Brincidofovir led to a complete, sustained clinical recovery, including osteomyelitis, probably attributed to reversal of adenovirus-induced immune dysregulation.